Age and sex dependent effects of early overnutrition on metabolic parameters and the role of neonatal androgens. Issue 1 (December 2016) - Argente-Arizón, Pilar; Ros, Purificación; Díaz, Francisca; Fuente-Martin, Esther; Castro-González, David; Sánchez-Garrido, Miguel; Barrios, Vicente; Tena-Sempere, Manuel; Argente, Jesús; Chowen, Julie
Abstract Background Males and females respond differently to diverse metabolic situations. Being raised in a small litter is reported to cause overnutrition that increases weight gain and predisposes an individual to metabolic disturbances in adulthood; however, existing data are inconsistent. Indeed, significant weight gain and/or metabolic disturbances, such as hyperinsulinemia and hyperleptinemia, are sometimes not encountered. We hypothesized that these inconsistencies could be due to the animal's sex and/or age at which metabolic parameters are measured. Methods To analyze the effects of neonatal overnutrition, male and female Wistar rats were raised in litters of 4 or 12 pups/dam and killed at postnatal days (PND) 10, 21, 30, 50, 85, or 150. In a second study to determine if neonatal sex steroid levels influence sex differences in metabolic parameters, female rats were treated with testosterone on PND1. Effects on weight, length, fat pads, adipokine production, and serum levels of glucose, metabolic hormones, and cytokines were analyzed in both studies. Results By PND10, both males and females raised in small litters had increased body weight, body length, adiposity, and serum glucose, insulin, leptin, and adiponectin levels. Females had a greater increase in inguinal fat, and males had higher expression of leptin messenger RNA (mRNA) and serum insulin, as well as increased testosterone levels. Most of the litter size effects diminished or disappeared after weaning and reappeared during adulthood in males, with sex differences in body size and adiposity being apparent postpubertally. Treatment of females with testosterone on PND1 tended to masculinize some metabolic parameters in adulthood such as increased body weight and serum leptin levels. Conclusions Our results indicate that (1) both sex and age determine the response to neonatal overnutrition; (2) differences in neonatal sex steroid levels may participate in the development of sex differences in metabolic parameters in adulthood and possibly in the response to neonatal overnutrition; and (3) the comparison of circulating hormone and cytokine levels, even in normal control animals, should take into consideration the early neonatal nutritional environment.